1974
DOI: 10.1111/j.1600-0609.1974.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Survival and Platelet Production in Idiopathic Thrombocytopenic Purpura (ITP) before and during Treatment with Corticosteroids

Abstract: Platelet mean life span (MLS) and platelet production were studied in 11 patients with idiopathic thrombocytopenic purpura (ITP) before and after institution of corticosteroids. Platelet MLS was greatly reduced before treatment. A prolongation of MLS was observed in every patient during corticosteroid therapy but there was in no case a normalization of platelet MLS. Platelet production was significantly above normal in untreated ITP and did not change significantly during corticosteroid treatment. The partial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1978
1978
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…These results showed that increased platelet production rates are uncommon in ITP patients, with most exhibiting either depressed or normal platelet production rates. A key question raised by this observation is why platelet production rates in ITP patients were rarely increased in these studies compared to prior studies, in which they were almost uniformly increased (Harker, 1970; Branehog & Weinfeld, 1974).…”
Section: Evidence For Decreased Platelet Productionmentioning
confidence: 69%
See 1 more Smart Citation
“…These results showed that increased platelet production rates are uncommon in ITP patients, with most exhibiting either depressed or normal platelet production rates. A key question raised by this observation is why platelet production rates in ITP patients were rarely increased in these studies compared to prior studies, in which they were almost uniformly increased (Harker, 1970; Branehog & Weinfeld, 1974).…”
Section: Evidence For Decreased Platelet Productionmentioning
confidence: 69%
“…The better labelling characteristics of 111 In versus 51 Cr allowed adequate radiolabelling with low platelet counts. This hypothesis is supported by survival data from paired autologous and allogeneic platelet survival measurements in 24 patients with ITP (Fig 1) (Abrahamsen, 1970; Branehog & Weinfeld, 1974; du P Heyns et al , 1986; Ballem et al , 1987). In these studies, when autologous platelet survival measured no more than 1 d ( n = 13), there was a significant and positive relationship ( r = 0·79; P = 0·001) between the two survival measurements (mean autologous platelet survival: 0·46 ± 0·33 d; mean allogeneic platelet survival: 0·40 ± 0·30 d).…”
Section: Evidence For Decreased Platelet Productionmentioning
confidence: 75%
“…Early thrombokinetic studies suggested that platelet production rates were increased in ITP, though these studies relied on allogeneic platelets labeled with Cr 5135;44 , a less effective platelet label. However, later studies in which allogeneic and autologous platelet survival were studied in the same individuals demonstrated significantly longer survival of autologous platelets 36;45;46 , particularly in patients in whom autologous platelet survival exceeded 1 day 9 . Platelet production rates estimated based on these latter studies led to the conclusion that platelet production is normal or decreased in most patients with ITP.…”
Section: Etiology and Pathogenesis: Causes And Mechanisms Of Primary mentioning
confidence: 97%
“…While conventional therapies such as corticosteroids and splenectomy primarily focus on reducing platelet destruction [30,31], the finding that platelet production is suboptimal in a substantial proportion of patients with ITP [32,33] has led to development of the TPO mimetics, which enhance platelet production and may therefore provide better outcomes [34].…”
Section: New Agents Have Changed the Treatment Paradigmmentioning
confidence: 99%